Pengaruh Pengetahuan Etika Bisnis Islam Karyawan Terhadap Etika Pemasaran Islam : Studi Kasus Karyawan Bank Muamalat KCP Baturaja - Muhamad Ongky Wijaya; Hilda Hilda; M. Junestrada Diem (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is to determine the effect of Islamic Business Ethics and the Understanding Level of Employee on Islamic Marketing Ethics (Case Study of Employees of Bank MuamalatBaturaja Sub-Branch Office).This study uses primary data with a quantitative approach. The population in this study amounted to 11employees of Bank Muamalat Baturaja Branch Office. Sampling in this study used a saturated sampling formula, so that 11 employees were sampled in this study. The analytical method used in this research is validity testing, reliability testing, classical assumption testing, and hypothesis testing using IBM SPSS 25 statistical analysis.The results of this study indicate that Islamic Business Ethics has a significant positive effect on Islamic Marketing Ethics and the understanding level of employees has no effect on Islamic Marketing Ethics while work discipline has a significant positive effect on Islamic Marketing Ethics, between Islamic Business Ethics and the Level of Understanding of Employees, the Level of Understanding of Employees is the most dominantly influence on the application of Islamic Marketing Ethics at Bank Muamalat Branch Office of Baturaja is Islamic Business Ethics.